2020
DOI: 10.1007/978-3-030-45237-7_10
|View full text |Cite
|
Sign up to set email alerts
|

What’s Decidable About Program Verification Modulo Axioms?

Abstract: We consider the decidability of the verification problem of programs modulo axioms -automatically verifying whether programs satisfy their assertions, when the function and relation symbols are interpreted as arbitrary functions and relations that satisfy a set of first-order axioms. Though verification of uninterpreted programs (with no axioms) is already undecidable, a recent work introduced a subclass of coherent uninterpreted programs, and showed that they admit decidable verification [26]. We undertake a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Recent work [10] has shown that verifying programs using uninterpreted abstractions can be extremely effective in practice for proving programs correct. Also, recent work by Mathur et al [40] explores ways to add axioms (such as commutativity of functions, axioms regarding partial orders, etc.) and yet preserve decidability of verification.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work [10] has shown that verifying programs using uninterpreted abstractions can be extremely effective in practice for proving programs correct. Also, recent work by Mathur et al [40] explores ways to add axioms (such as commutativity of functions, axioms regarding partial orders, etc.) and yet preserve decidability of verification.…”
Section: Discussionmentioning
confidence: 99%
“…The verification of uninterpreted programs is undecidable in general; for the subclass of coherent uninterpreted programs, however, it is decidable [15]. The verification problem of uninterpreted programs has been extended with theories, i.e., with axioms over the functions and predicates [16]. Adding axioms to coherent uninterpreted programs preserves decidability for some axioms, e.g., idempotence, while it yields undecidability for others, e.g., associativity.…”
Section: Related Workmentioning
confidence: 99%
“…This work stems from the recent decidability result on uninterpreted coherent programs [Mathur et al 2019a], which has also been extended to incorporate reasoning modulo theories including associativity and commutativity of functions over the data domain and ordering relations on the data domain [Mathur et al 2019b]. In our work we use automata-theoretic techniques that, over the data domain, reason about equality and function computation over the data elements.…”
Section: Related Workmentioning
confidence: 99%